The paradox of mobility for older people in the rural-urban fringe. (August 2019) - Peacock, Adam; Pemberton, Simon
Abstract: Whilst considerable focus has been placed on mobility in rural and urban areas, there has been little attention to date on individuals' experiences and practices of mobility in the rural-urban fringe (RUF). This is surprising given that mobility is a defining feature of the RUF, and with such landscapes often experienced at speed. Through a focus on older people living in a RUF locality, the paper makes three important contributions. First, it highlights the range of mobilities and mobility infrastructures that may be available to older residents in the RUF, as well as their ability to access such features. Second, it also identifies the importance of 'proximity' in shaping older people's mobilities in the context of the RUF and how a rural-urban fringe (mobility) idyll may exist for many older people. Finally, the paper illustrates a paradox in that the very nature of the RUF as a transitory and chaotic space may undermine older people's mobility experiences and practices over time. Highlights: New insight into experiences and practices of mobility in the rural-urban fringe (RUF). Highlights range of mobilities and mobility infrastructures in the RUF. Identifies importance of 'proximity' in shaping older people's mobilities. Discusses a rural-urban fringe (mobility) idyll. Paradox in that the RUF as transitory and chaotic undermines mobility over time.